Applying Physics in Mountaineering: Analyzing the Interplay between Education, Experience, and Physics Concept Awareness - Al-Qoyyim, Thufail Mujaddid; Abadi, Muhammad; Rahmat, Solihin; Wahyudi, Wahyudi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study evaluates the influence of education and climbing experience on the awareness and understanding of physics concepts among mountain climbers. Climbing requires an understanding of physics concepts such as air pressure, friction, potential energy, and heat transfer. Using a descriptive quantitative survey method, this study involved 109 climbers with diverse educational backgrounds and levels of experience. The questionnaire assessed the relationship between awareness of physics concepts, climbing experience, and respondents' educational levels, employing regression analysis. The results indicated that climbing experience does not significantly affect physics awareness, showing a very weak negative correlation between the duration and frequency of climbing and physics understanding. Formal education also did not show a significant influence on the awareness or application of physics concepts in climbing. However, there was a weak positive correlation between physics awareness and the ability to overcome physical challenges. It is recommended to enhance education and outreach regarding the relevance of physics in climbing, including practical guides and applicable training programs to improve climbers' skills and safety.